Implementasi Pembayaran dengan PSP Pengganti Uang Kertas Studi Kasus di Madrasah Sains Quran Ar Ridwan Bojonegoro - Al Fahmi, Moh. Dhofir Jenny (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
The development of technology is currently quite rapid, bringing about major changes in various aspects of human life. One of the innovations in technological progress today is the Payment Service Provider (PSP). PSP is currently used in several institutions, one of which is in Islamic boarding schools. In the era of globalization and digitalization, the use of Payment Service Providers (PSP) which is used as a payment method to replace paper money offers an innovative and efficient solution. The purpose of this study was to determine the implementation of payments with PSP to replace paper money at Madrasah Ibtidaiyah Al-Qur'an Ar Ridwan Bojonegoro. The method used in this study is a qualitative method with a case study type. Data collection techniques in the study were carried out by in-depth interviews with financial managers and users of the PSP program at Madrasah Ibtidaiyah Al-Qur'an Ar Ridwan Bojonegoro. The results of the study revealed that the implementation of financial digitalization through the use of PSP in managing student finances brings various important benefits. Among them are the ease of recording and reporting finances that are more transparent between the boarding school, guardians of students, and students themselves. Not only does it provide benefits, but the use of PSP also has its drawbacks, namely the card is easily lost and can only be used at the Ar Ridwan institution. In general, the use of PSP Mobile makes it easier for students to manage their personal finances more effectively and efficiently..